Structures - Schodek, Daniel L. 1941-; Bechthold, Martin (Pearson, 2014)
Structures, Seventh Edition, offers single-volume coverage of all major topics in structural analysis and design. Focusing on how structures really work, the text discusses concepts from both engineering and architectural perspectives, exploring structural behavior, structural analysis, and design within a building context.